Effect of Intraumbilical Oxytocin on Duration of Third Stage of Labour - Tabinda Khalid (Journal of Rawalpindi Medical College, 2017)
Background:To determine the efficacy of intraumbilical oxytocin in reducing duration of third stage of labor, compared to routine active management of third stage of labor(AMTSL). Methods: In this randomized controlled trial one hundred parturient women were divided in two groups consisting of 50 each. Active management of third stage was done in both the groups. The study group in addition to active management, received oxytocin 10 international units( IU) diluted in 10ml normal saline through the umbilical vein and control group received equal volume of normal saline as placebo .The mean time taken for the completion of third stage was calculated for both groups in terms of minutes. The mean time “t” between the two groups was compared using Independent sample- t test. P value<0.05 was taken significant. Results: The mean duration of third stage of labor was 4.38±0.88 minutes in the study group, compared to 5.12±1.32 minutes in the control group which was significant statistically p=0.001. There was no incidence of retained placenta and none of placenta remain undelivered beyond 15 minutes in both groups. Conclusion: Intraumbilical oxytocin when given along with active management significantly reduces the mean duration of third stage of labour, compared to active management alone.